Similar but distinct: The impact of biomechanical forces and culture age on the production, cargo loading, and biological efficacy of human megakaryocytic extracellular vesicles for applications in cell and gene therapies - Will Thompson; Eleftherios Terry Papoutsakis (Wiley, 2023)
Abstract Megakaryocytic extracellular vesicles (MkEVs) promote the growth and megakaryopoiesis of hematopoietic stem and progenitor cells (HSPCs) largely through endogenous miR‐486‐5p and miR‐22‐3p cargo. Here, we examine the impact of biomechanical force and culture age/differentiation on the formation, properties, and biological efficacy of MkEVs. We applied biomechanical force to Mks using two methods: shake flask cultures and a syringe pump system. Force increased MkEV production in a magnitude‐dependent manner, with similar trends emerging regardless of whether flow cytometry or nanoparticle tracking analysis was used for MkEV counting. Both methods produced MkEVs that were relatively depleted of miR‐486‐5p and miR‐22‐3p cargo. However, while the shake flask‐derived MkEVs were correspondingly less effective in promoting megakaryocytic differentiation of HSPCs, the syringe pump‐derived MkEVs were more effective in doing so, suggesting the presence of unique, unidentified miRNA cargo components. Higher numbers of MkEVs were also produced by "older" Mk cultures, though miRNA cargo levels and MkEV bioactivity were unaffected by culture age. A reduction in MkEV production by Mks derived from late‐differentiating HSPCs was also noted. Taken together, our results demonstrate that biomechanical force has an underappreciated and deeply influential role in MkEV biology, though that role may vary significantly depending on the nature of the force. Given the ubiquity of biomechanical force in vivo and in biomanufacturing, this phenomenon must be grappled with before MkEVs can attain clinical relevance.